The Relationship between Breakfast Habits and Nutritional Status with Learning Achievement in Strada Nawar Bekasi Junior High School Students - Said, Avicenna Muhammad; Latersia, Yovicristy; Muniroh, Lailatul (Universitas Airlangga, 2024)
Learning achievement is a form of evaluation based on the results obtained in the process of gaining knowledge. Learning achievement can be influenced by various factors, both environmental and health factors, such as breakfast habits and nutritional status. The aim of this research was to analyzed the relationship between breakfast habits and nutritional status with learning achievement in junior high school students. This study was an analytical observational research using a cross-sectional study design. The research was conducted at Strada Nawar Bekasi Junior High School from September to December 2022 with the sample being students from grades VII and VIII. The sample was chosen randomly using proportionate random sampling with a total of 81 students based on inclusion and exclusion criteria. The data collected include height and weight through anthropometric measurements, interviews breakfast habits using the SQ-FFQ form, and student report cards for the last semester. The data obtained was then tested with SPSS software using Chi-square test analysis. The results showed that there were students with good breakfast habits (77.8%), overnutritional status (40.8%), and good learning achievement (48.1%). From this research, it was found that there was a relationship between breakfast habits (p-value = 0.041) and there was no relationship between nutritional status (p-value = 0.190) with learning achievement. It was concluded that the good of breakfast habits is directly proportional to the student's learning achievement and there is no relationship between nutritional status and student's learning achievement.